A Survey of Minimally Invasive Surfactant Use in the United States - Ahn, Natasha; Derrick, Matthew; Hussain, Walid (American Journal of Perinatology, 2024)
Minimally invasive surfactant therapy (MIST) has become the standard of care in delivering surfactant noninvasively in many parts of the world, particularly throughout Europe; however, centers in the United States have been slower to adopt it. The most recent assessment of the use of MIST in the United States was in 2018 by Kurepa et al. Considering the increasing evidence favoring MIST, this paper reassessed the current rate of utilization and aims to examine barriers to MIST implementation.A web-based survey was distributed to approximately 4,500 individuals in the American Academy of Pediatrics Section of Neonatal-Perinatal Medicine (AAP SoNPM) mailing list. The questions were aimed at addressing MIST usage in the United States, examining barriers for neonatology providers to implement MIST into their practice, and determining the use of sedation during the MIST procedure.Of the 381 respondents, 39% used MIST as part of their practice, which was an increase from 15% in 2018. The most prevalent barrier to implementation was the lack of procedural training. There was a large increase in the use of sedation for the procedure compared with 2018.MIST use among AAP SoNPM respondents has more than doubled since 2018; InSurE (INtubation-SURfactant delivery Extubation) remains the most prevalent method of surfactant delivery in non-intubated patients. The list of different types of barriers and comments provided by respondents can be a resource for units planning to implement MIST.
Keywords: MIST; surfactant; survey; implementation barriers